Study on Transorgan Regulation of Intervertebral Disc and Extra-Skeletal Organs Through Exosomes Derived From Bone Marrow Mesenchymal Stem Cells - Wang, Zhikun; Wu, Yangming; Zhao, Zhonghan; Liu, Chengyi; Zhang, Lingli (Frontiers in Cell and Developmental Biology, 2021)
Exosomes are membranous lipid vesicles that fuse with intracellular multicellular bodies and then release into the extracellular environment. They contain a variety of bioactive substances, including proteins, mRNA, miRNAs, lncRNAs, circRNAs, lipids, transcription factors and cytokine receptors. Under certain conditions, bone marrow mesenchymal stem cells (BMSCs) can differentiate into osteoblasts, chondrocytes, adipocytes, and their biological functions are mainly performed by paracrine or endocrine approaches. Therefore, the research on exosomes derived from BMSCs (BMSC-Exos) have attracted extensive attention. In this review, we introduced the mechanism of BMSC-Exos regulating the proliferation and differentiation of osteoblasts and osteoclasts through mRNA, miRNA, lncRNA, circRNA and so on was discussed in detail. We also reviewed the current studies about the impact of BMSC-Exos on human organs. They have significant therapeutic effects on the motor system, cardiovascular system, and nervous system. If exosomes are used as research targets, they can play a prominent role in intervertebral disc degeneration, tendon regeneration, wound repair, cardiovascular system protection, nerve injury treatment, and clinical disease diagnosis. In the end, we discussed the regulatory effects of exosomes from extraosseous sources on BMSCs, and sort out and improve the regulatory activity network of exosomes secreted by extraosseous organs and tissues on BMSCs. This study provides a theoretical basis for the application of BMSC-Exos in the field of bone and exploring different sources of exosomes to improve bone microenvironment and resist bone metastasis of tumor cells. At the same time, it also provides a new idea for the prevention and rehabilitation of human diseases by exosomes.